Critique of the new NBN policy: Lower cost, faster roll-out, access competition, technology independence, future proof? - Shepherd, Graham (Journal of Telecommunications and the Digital Economy, 2020)
In December 2014 the Australian Minister for Communications released a policy destined to transform the NBN as conceived by the previous government. Its primary stated aims are to lower costs and introduce competition. The cost reductions are driven by significantly compromising the access speed and substantially but not entirely eliminating the lead-in cost. The policy also anticipates a competitive model, which risks creating islands of monopoly based upon the footprints of the proposed FTTN and HFC networks – although the fixed wireless and satellite technologies should be able to operate competitively, if not profitably. This paper addresses the limitations of the policy as currently stated and proposes some changes in approach which share the objectives of the policy but without compromising access speed. The changes will eliminate the lead-in cost entirely and will introduce infrastructure competition in the long-term interests of end-users. They will accelerate the NBN roll-out and ensure that the national infrastructure is responsive to future technologies, market demands and business opportunities.